Set-membership identifiability of nonlinear models and related parameter estimation properties - Jauberthie, Carine; Travé-Massuyes, Louise; Verdiere, Nathalie (Zielona Góra: Uniwersytet Zielonogórski)
Identifiability guarantees that the mathematical model of a dynamic system is well defined in the sense that it maps unambiguously its parameters to the output trajectories. This paper casts identifiability in a set-membership (SM) framework and relates recently introduced properties, namely, SM-identifiability, [My]-SM-identifiability, and [Epsilon]-SM-identifiability, to the properties of parameter estimation problems. Soundness and [Epsilon]-consistency are proposed to characterize these problems and the solution returned by the algorithm used to solve them.
Keywords: identifiability; bounded uncertainty; set-membership estimation; nonlinear dynamic models